Efficient removal of Pb(II) ion using TiO2 /ZnO/SiO2 nanocomposite from aqueous solutions via adsorption-photocatalysis process - Hadian, Dadan; Alni, Anita; Patah, Aep; Handayani, Nurrahmi; Zulfikar, Muhammad Ali (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research aims to investigate the usage of a TiO2 /ZnO/SiO2 (TZS) composite prepared via a 24-h hydrothermal process at 180° C to remove Pb(II) through adsorption-photocatalysis. Pb(II) exposure has known health risks, making this study significant. The research explores the impact of pH, the nanocomposite quantity, and contact time in the process. Adsorption-photocatalysis was carried out in the dark for 60 min, followed by irradiation with a 160-watt mercury lamp. The adsorption process of Pb(II) ion removal adhered to the pseudo-second-order model regarding kinetics, while the adsorption isotherm corresponded to the Freundlich isotherm. Additionally, the assessment of photocatalysis kinetics showed that the removal of Pb(II) ions followed a pseudo-first-order model, resulting in a 99.58% elimination of Pb(II) ions. Post-adsorption-photocatalytic treatment, a yellowish precipitate was observed. The XRD pattern result of the yellowish precipitate confirmed the presence of PbO as the formed Pb phase. The study concludes that the TiO2 /ZnO/SiO2 nanocomposite as adsorbent-photocatalyst is a highly effective, efficient, and promising method to remove Pb(II) contamination from aqueous solutions.